Effects of soil pasteurization and soil N status on severity of Striga hermonthica (Del.) Benth. in maize - Ahonsi, M.; Berner, D.; Emechebe, A.; Lagoke, S.T.O. (2002)
The nature of interrelationships between soil pasteurisation, and increased soil N content, on the severity of Striga hermonthica infection in maize was studied in pot experiments in the screen-house. An initial experiment revealed that there was no significant difference in amount of S. hermonthica infection in maize grown in potted soil collected from Bida (9°05′N, 6°01′E) and Ibadan (7°17′N, 3°30′E). However, there was 57% increase in amount of S. hermonthica infection and a 68% reduction in maize shoot dry matter when maize was grown in pasteurised soil compared with natural soil. In another experiment, soil steaming significantly influenced the effects of increased soil N fertility (from preceding soybean cv. SAMSOY-2 or application of 90 kg N ha−1) on severity of S. hermonthica in maize. In natural soil, application of N to maize reduced (by 53%) the number of emerged S. hermonthica plants and increased (by 154%) maize dry matter compared with no fertilizer application. In pasteurised soil, application of N to maize increased S. hermonthica severity by 26% and also significantly increased maize dry matter compared with no fertilizer application. The same effects were observed when soybean was used to increase soil N content. Analysis of natural and pasteurised soil revealed only minor differences in composition of K+, Na+, Cu, Mn, and Fe, and none of these changes was directly related to S. hermonthica infection in maize. Results of this study indicate that the differences in S. hermonthica infection in pasteurised and natural soil could be attributed to soil biotic factors that reduce S. hermonthica infection in natural soil. The results partly provide an explanation for the wide variation in reports on the effects of N fertilization on severity of S. hermonthica infection and stress the need for understanding the mechanisms of natural reduction in S. hermonthica infection and interactions of these natural mechanisms with other control techniques.